(untitled) (Journal of Pharmaceutical Negative Results, 2022)
AIM: To evaluate and compare the sealing ability of newly introduced C Point and Protaper Gutta PerchaMATERIAL AND METHODOLOGY: A total of 30 freshly extracted human mandibular second premolar was selected, and their crowns were cut. The root canal of each sample was instrumented using a rotary crown down technique and then divided into two experimental (n = 10 each) and one control group (n = 10). Samples in the experimental groups were filled as follows: Group 1, Protaper Gutta Percha; group 2, single-cone C-points/ Endosequence bioceramic-sealer; group 3, control group after 7 days, the sealing ability of root canal fillings was tested at different time intervals using glucose leakage model. Glucose leakage values were measured using a spectrophotometer and statistically analyzed.Results: The control group showed no detectable glucose leakage throughout the experiment, Glucose leakage was evident in both the groups (Group 1, Group 2) with non-significant difference after 1 and 2 week and with significant difference after 3 week.Conclusion: Newly introduced C Point have shown significantly lesser leakage as compared to the gold standard gutta-percha obturation system